Parrots over Puerto Rico - Roth, Susan L.; Trumbore, Cindy (Parrots, 2013)
"A combined history of the Puerto Rican parrot and the island of Puerto Rico, highlighting current efforts to save the Puerto Rican parrot by protecting and managing this endangered species"--Provided by publisher.